Representasi Perempuan melalui Perspektif Sara Mills dalam Media Detik.Com dan Kompas.com - Teti Sobari; Irma Silviani (Universitas Muhammadiyah Surabaya, 2019)
The background of this research was the emergence of woman discourse that was often becoming a cornered object, considered as wrong and a negative gender stereotype. The objectives were to find out how woman’s representation through Sara Mills perspective on the Sisca’s murder discourse, the subject-object and readers position on the news about Sisca’s murder in two online media. The news about Sisca’s murder at the Kebagusan City apartment Jakarta, on December 18th 2018, became the material object of this research. The data was analyzed by using Sara Mills perspective. The results showed that woman’s representation included weak woman, marginalized woman, bad woman and false women. In addition, the results showed that the text that become data put man as a subject and woman as an object. The readers were directed to position themselves as a man